Circulating 25-hydroxyvitamin D level and risk of developing rheumatoid arthritis - Hiraki, Linda T. (Rheumatology (Oxford), 2014)
Objective. The aim of this study was to examine the relationship between preclinical circulating 25-hydroxyvitamin D [25(OH)D] and RA in two nested case–control studies within the prospective cohort Nurses’ Health Study (NHS) and NHS II (NHSII). Methods. We included 166 women with RA and blood specimens collected 3 months to 16 years prior to the first RA symptom and 490 matched controls (3:1, matched on age, date of blood draw, hormonal factors). We calculated the odds ratio (OR) and 95% CI for incident RA using conditional logistic regression multivariable adjusted models, including additional covariates for smoking status, parity and breastfeeding, alcohol consumption, BMI, median income and region of residence in the USA. We repeated analyses stratified by time from blood draw to RA diagnosis (3 months to <4 years or ≥4 years) and meta-analysed estimates from the two cohorts using fixed effects models. Results. Incident RA was confirmed in 120 NHS [mean age 63.8 years (s.d. 8.2)] and 46 NHSII participants [mean age 48.5 years (s.d. 4.7)]. Mean time from blood draw to RA diagnosis was 7.8 years (s.d. 4.2) for NHS and 4.2 years (s.d. 2.0) for NHSII participants. Meta-analysis of crude and multivariable-adjusted conditional logistic models did not show significant associations between circulating 25(OH)D and RA. However, among NHSII women with blood drawn between 3 months and <4 years prior to RA diagnosis, there was a 20% decreased risk of RA associated with each 1 ng/ml increase in 25(OH)D [OR 0.80 (95% CI 0.64, 0.99)]. Conclusion. We did not observe a significant association between circulating 25(OH)D levels and RA, except for among a small subset of NHSII women with levels measured closest to RA diagnosis.